Impact of steam treatment on shelf‐life stability of a xanthone‐rich green herbal tea (Cyclopia maculata Andrews Kies) – identifying quality changes during storage. (16th October 2018) - Alexander, Lara; de Beer, Dalene; Muller, Magdalena; van der Rijst, Marieta; Joubert, Elizabeth
Abstract: BACKGROUND: Steam treatment of shredded, fresh C. maculata (honeybush) plant material improves the aroma of this green herbal tea with a slight impact on color and phenolic content, but the effect on storage stability is not known. RESULTS: Steam‐treated (60 s before drying) and untreated (control) dried plant material was stored under normal storage conditions in semi‐permeable sachets at 25 °C and 60% relative humidity. Reference samples of treated (steamed) and untreated (control) material were stored at 0 °C in impermeable pouches for maximum retention of quality. The stability of the herbal tea was assessed in terms of sensory profile, phenolic composition and color over a storage period of 6 months. Normal storage conditions resulted in a significant ( P < 0.05) decrease in green color, especially in steamed samples. Intensities of fruity and sweet‐associated aroma attributes increased progressively during storage, while the opposite was observed for vegetal and cereal‐like attributes. These changes in the aroma profile were more pronounced in untreated (control) samples. Individual phenolic content remained stable during storage. CONCLUSIONS: Storage of 3 to 6 months may result in a more appealing aroma profile and enhanced product quality, despite loss of green color. © 2018 Society of Chemical Industry